A paisagem do Cerrado cabe em um desenho? Uma proposta metodológica do conceito paisagem-lugar para a mediação didática da Geografia dos anos iniciais - Queiroz, Fabiana Rodrigues Oliveira (2020)
Geography as a science that deals with the analysis of geographic space through its conceptual mediators, is also a curricular component present in Basic Education and participates in the processes of human constitution. Their knowledge can favor critical and reflective reading of reality and provide specific ways of thinking and reasoning geographic spatiality. In this process, children, as social actors with histories and geographies, officially approach the school form of this science in Elementary School I, segment in which the teacher Pedagogo to act. Thus, an evidente relationship between Geography, Childhood and School Education raises the need to broaden views about teaching Geography with children. What gives this research the opportunity to analyze the didactic mediation the teacher Pedagogo in the processo of teaching Geographyand the potential of the language of drawing and of the concept of landscape of the place for the processes of mediation didactic and for the production of knowledge geographic (cognitive mediation), in this school segment. For this, the research was supported by references in the field of Education, particularly in the historical-cultural theory and in the theoretical contributions of the field of Teaching Geography in dialogue with the Geography of Childhood. It is of a qualitative nature, being of the participant genre and guided by the socio-historical-geographical research approach. Dialectics is the basic principle for the interpretation and analysis of results, allowing, at the same time, to value the social actors involved in the teaching-learning processes and the geographic knowledge itself. The field research had as its locus two public schools in the municipal education network of Goiânia, Goiás. It counted with the participation two teachers pedagogas and 41 children from the 4th and 5th year of Elementary Education, in the age group of 9 to 12 years, in 2018 and 2019, respectively. Participant observation was adopted as one of the methodological instruments that allowed direct observation of classes and the carrying out of didactic interventions in both classes. Other research techniques were also included in the research, such as: open semi-structured interview, questionnaire, autobiographical narrative and evaluative narrative, carried out with the teachers.In addition, diagnostic and evaluative narratives were developed with the children through drawings.The data revealed, on the one hand, the power of the language of drawing, as one of the logics present in childhood that mobilizes children's motives, as it articulates to the pedagogical process, a sensitive knowledge of an artistic dimension that brings together imagination, creation and creativity.On the other hand, it revealed the geographical landscape of the place as a conceptual and methodological dimension that, together with the drawing, constitutes a powerful methodological proposal for mediation processes (didactic and cognitive), because it carries elements of a social and physical-natural nature.With this, the design raised the condition of the geographical language, becoming the geographical design and the landscape of the place assumed the definition of landscape-place. However, the potential of design and landscape is still under-evidenced, especially in the set of research on teaching Geography in the early years. Still, as part of the results, principles emerged that can guide the pedagogical practices of professor pedagogo, from the perspective of mediation.Such principles are interrelated and are developed in actions that can subsidize and favor the teaching-learning process of Geography with children, namely: 1) The inseparability between theory and practice; 2) Relationships oriented by otherness; 3) Teaching as a responsive act; 4) Teaching as mediation of cognitive mediation; 5) Conscious and intentional planning; 6) Landscape-place as a conceptual and methodological construction.